2015
DOI: 10.1007/s11162-015-9396-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Changing Dynamics of the Gender Gap in Undergraduate Engineering Majors: 1971–2011

Abstract: In this paper we examine the level and determinants of entering college students' plans to major in engineering. While the overall level of interest in engineering has fluctuated between 1971 and 2011, a very large gender gap in freshman interest remains. We find that the percent of first-year women who plan to major in engineering is roughly the same today as in the early 1980s. We estimated the impact of predictor variables for five time points : 1976, 1986, 1996, 2006 and 2011. Independent variables were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 44 publications
2
30
0
3
Order By: Relevance
“…This finding is interesting, considering that self-efficacy has been long established as a reliable and important precursor to students' academic aspirations and achievement (e.g., Hackett, 1985; Lent et al, 2015), especially in STEM fields (Heinze and Hu, 2009; Larson et al, 2015; Sax et al, 2016). It is plausible that first-generation two-year college women are more inclined to pursue STEM fields for reasons beyond their self-perceptions of their math abilities.…”
Section: Discussionmentioning
confidence: 90%
“…This finding is interesting, considering that self-efficacy has been long established as a reliable and important precursor to students' academic aspirations and achievement (e.g., Hackett, 1985; Lent et al, 2015), especially in STEM fields (Heinze and Hu, 2009; Larson et al, 2015; Sax et al, 2016). It is plausible that first-generation two-year college women are more inclined to pursue STEM fields for reasons beyond their self-perceptions of their math abilities.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have found that most women in engineering majors do go into engineering careers, and most women in the biological sciences aspire to earn a terminal medical degree and go into health care; however, women in computing and physical sciences are more diffuse in their career interests (Kahn & Ginther, ; Lehman et al., ; Morgan, Gelbgiser, & Weeden, ; Sax et al., ). Similarly, women majoring in math are far less likely to be interested in continuing onto the graduate school in mathematics and are instead drawn to careers in business or K‐12 education (Sax et al., ; Snyder, Dillow, & Hoffman, ).…”
Section: Understanding Women Across Stem: What Do We Already Know?mentioning
confidence: 99%
“…However, there is evidence that the effects of self‐concept and sense of belonging differ among various STEM fields. In one study, women with high math self‐concept were most likely to major in physics than in other STEM fields (Sax et al., ); however, Margolis, Fisher, and Miller (1997) have noted that confidence and self‐efficacy have also been observed as critical components to women's persistence in computing and technology. Further, while baseline math self‐concept and sense of belonging may influence women's initial pursuit of particular majors, Sax () found that selection of a physics or engineering majors was associated with an increase in women's mathematical self‐concept, demonstrating the reciprocal relationship between self‐concept and selecting a particular field.…”
Section: Understanding Women Across Stem: What Do We Already Know?mentioning
confidence: 99%
“…This is particularly concerning given that, overall, women account for 57% of undergraduate degrees conferred (Sax et al 2016). The proportion of women graduating from engineering disciplines increased dramatically between 1950, when women accounted for 0.3% of all undergraduate engineering degrees conferred, and 2014, when women accounted for 18.4% of undergraduate engineering degrees (National Center for Education and Statistics 2014).…”
Section: Women In Engineeringmentioning
confidence: 99%
“…It is therefore not surprising that students who display strong community orientation are less likely to opt into engineering fields (Diekman et al 2010). Fortunately, the degree to which a communal focus deters women from pursuing engineering has been decreasing over time (Sax et al 2016). This may be due to increased attempts to emphasize the benefits that engineers bring to society.…”
Section: Community Orientationmentioning
confidence: 99%